2014
DOI: 10.3168/jds.2014-8359
|View full text |Cite
|
Sign up to set email alerts
|

Effects of colostrum versus formula feeding on hepatic glucocorticoid and α1- and β2-adrenergic receptors in neonatal calves and their effect on glucose and lipid metabolism

Abstract: Neonatal energy metabolism in calves has to adapt to extrauterine life and depends on colostrum feeding. The adrenergic and glucocorticoid systems are involved in postnatal maturation of pathways related to energy metabolism and calves show elevated plasma concentrations of cortisol and catecholamines during perinatal life. We tested the hypothesis that hepatic glucocorticoid receptors (GR) and α 1 -and β 2 -adrenergic receptors (AR) in neonatal calves are involved in adaptation of postnatal energy metabolism … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
2
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 71 publications
(132 reference statements)
1
22
2
1
Order By: Relevance
“…However, the leptin concentrations in colostrum and in plasma of neonatal piglets were not correlated (Woliński et al, 2014), whereas we observed a weak correlation (ρ = 0.3; P < 0.05; n = 57) in dairy calves. The role of colostral leptin seems less clear, as the increase of serum leptin observed in the present study upon colostrum intake was not observed in 2 other studies (Blum et al, 2005;Schäff et al, 2014); however, this might have been due to the relatively small animal numbers in these studies, which did not allow for picking up the small and transient increase we were able to show herein. When comparing calves receiving only MR with colostrum-fed calves, the leptin concentrations were lower in MR-fed calves (Schäff et al, 2014).…”
Section: Hormonescontrasting
confidence: 90%
See 1 more Smart Citation
“…However, the leptin concentrations in colostrum and in plasma of neonatal piglets were not correlated (Woliński et al, 2014), whereas we observed a weak correlation (ρ = 0.3; P < 0.05; n = 57) in dairy calves. The role of colostral leptin seems less clear, as the increase of serum leptin observed in the present study upon colostrum intake was not observed in 2 other studies (Blum et al, 2005;Schäff et al, 2014); however, this might have been due to the relatively small animal numbers in these studies, which did not allow for picking up the small and transient increase we were able to show herein. When comparing calves receiving only MR with colostrum-fed calves, the leptin concentrations were lower in MR-fed calves (Schäff et al, 2014).…”
Section: Hormonescontrasting
confidence: 90%
“…The role of colostral leptin seems less clear, as the increase of serum leptin observed in the present study upon colostrum intake was not observed in 2 other studies (Blum et al, 2005;Schäff et al, 2014); however, this might have been due to the relatively small animal numbers in these studies, which did not allow for picking up the small and transient increase we were able to show herein. When comparing calves receiving only MR with colostrum-fed calves, the leptin concentrations were lower in MR-fed calves (Schäff et al, 2014). However, it is improbable that individual adipokines, such as leptin or adiponectin, out of a plethora of other bioactive components contained in colostrum would alone mediate the beneficial (not immune globulin-related) effects commonly associated with colostrum intake.…”
Section: Hormonescontrasting
confidence: 90%
“…Both hormones are highly concentrated in first colostrum (Kesser et al, 2015(Kesser et al, , 2017, and the absorption of adiponectin from first colostrum was recently shown in neonatal calves (Kesser et al, 2015). Leptin absorption from colostrum was less clear in previous studies, but an elevated plasma concentration of leptin was also associated with colostrum feeding (Blum et al, 2005;Schäff et al, 2014;Kesser et al, 2017). Absorption of colostral leptin occurs in rats and humans (Szymeczko et al, 2009;Woliński et al, 2014;Palou et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Greater heat production at birth was probably the consequence of the metabolic activity of the brown fat tissue that decreased with time (Vermorel et al, 1983). The thyroid hormones stimulate thermogenesis, and the decrease in plasma T 3 and T 4 during the neonatal period is in line with the lower heat production at 7 and 8 d of age (Silva, 2006;Hammon et al, 2012;Schäff et al, 2014). The greater heat production at feeding times might be a result of greater physical activity and, in addition, of stimulating digestive processes in the gastrointestinal tract at that time (Vermorel et al, 1983).…”
Section: Discussionmentioning
confidence: 99%
“…Besides lactose, colostrum supplies the neonate with fat, since colostrum, as a highfat diet, provides the bulk of energy required for the hepatic oxidation of fatty acids [111]. The induction of this pathway occurs because of an increase in the activities of enzymes involved in the mitochondrial oxidation of fatty acids.…”
Section: Carbohydrate Metabolism and Energy Homeostasismentioning
confidence: 99%